Fibrinolysis in Traumatic Brain Injury: Diagnosis, Management, and Clinical Considerations - Anderson, Taylor N.; Farrell, David H.; Rowell, Susan E. (Seminars in Thrombosis and Hemostasis, 2021)
Posttraumatic coagulopathy involves disruption of both the coagulation and fibrinolytic pathways secondary to tissue damage, hypotension, and inflammatory upregulation. This phenomenon contributes to delayed complications after traumatic brain injury (TBI), including intracranial hemorrhage progression and systemic disseminated intravascular coagulopathy. Development of an early hyperfibrinolytic state may result in uncontrolled bleeding and is associated with increased mortality in patients with TBI. Although fibrinolytic assays are not routinely performed in the assessment of posttraumatic coagulopathy, circulating biomarkers such as D-dimer and fibrin degradation products have demonstrated potential utility in outcome prediction. Unfortunately, the relatively delayed nature of these tests limits their clinical utility. In contrast, viscoelastic tests are able to provide a rapid global assessment of coagulopathy, although their ability to reliably identify disruptions in the fibrinolytic cascade remains unclear. Limited evidence supports the use of hypertonic saline, cryoprecipitate, and plasma to correct fibrinolytic disruption; however, some studies suggest more harm than benefit. Recently, early use of tranexamic acid in patients with TBI and confirmed hyperfibrinolysis has been proposed as a strategy to further improve clinical outcomes. Moving forward, further delineation of TBI phenotypes and the clinical implications of fibrinolysis based on phenotypic variation is needed. In this review, we summarize the clinical aspects of fibrinolysis in TBI, including diagnosis, treatment, and clinical correlates, with identification of targeted areas for future research efforts.
Keywords: traumatic brain injury; fibrinolysis; coagulopathy; intracranial hemorrhage; thromboelastography